Scientific and technical information on organic farming: assessment of selected bibliographic indicators in database CAB Abstracts - Tomaž BARTOL; Špela DRNOVŠEK; Majda ČERNIČ-ISTENIČ (Acta Agriculturae Slovenica)
We scientometrically examined selected publishing patterns in organic farming as indexed by database CAB Abstracts (CABA) in the period 1973-2003. Some characteristics of CABA were also established. 4,170 records of all types (2,740 journal articles, 1,165 conference papers etc.) were harvested with the employment of descriptors derived from the CAB Thesaurus. The journal articles were further analyzed for yearly growth, languages, authorship, and geographic location. Growth has accelerated during the last ten years. English prevails among the 31 retrieved languages, with some 50 % citations, followed by German, Italian, French, and Japanese. A few highly productive authors (among the 4,304 different authors), with some publishing as many as 18 articles, accounted for the core of documents, whereas as many as 3,438 authors contributed only one article in the entire period. Germany was most frequently indexed as a geographic-location-descriptor, followed by Italy, U.K., Denmark, and Switzerland. This descriptor field, however, is not employed consistently so the geographic data must be interpreted with caution. This analysis is based mostly on descriptor Organic farming so some other terms could possibly also be employed to retrieve more documents related to this field of research.